2001
DOI: 10.1303/jjaez.2001.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Unusual Hot Weather on the Occurrence of Several Arthropod Crop Pests.

Abstract: Abstract:In order to project the influence of global climatic changes on insects, we examined the effects of a rise in temperature of 2-3°C on the phenology and occurrence of arthropod crop pests using data obtained from Kagoshima Prefecture, southwestern Japan, in 1998. The average temperature of this year was 2°C higher than that between 1960-1998. Several arthropod species emerged earlier than previous years because of the unusually high average temperature. These species were Homona magnanima, Adoxophyes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Species with a high T 0 for preoviposition period tend to have increased reproductive activity. Yamaguchi et al (2001) demonstrated that high temperature in early spring accelerates the appearance of overwintering insects especially in those species with low T 0 .…”
Section: Potential Increase In the Number Of Generations And Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Species with a high T 0 for preoviposition period tend to have increased reproductive activity. Yamaguchi et al (2001) demonstrated that high temperature in early spring accelerates the appearance of overwintering insects especially in those species with low T 0 .…”
Section: Potential Increase In the Number Of Generations And Densitymentioning
confidence: 99%
“…The effects of environmental changes on arthropods have been reviewed and discussed extensively (Kiritani, 1988(Kiritani, , 1991(Kiritani, , 1999(Kiritani, , 2001Cammell & Knight, 1992;Kareiva et al, 1993;Harrington & Stork, 1995;Heong et al, 1995;Morimoto et al, 1998;Yamamura & Kiritani, 1998;McCarty, 2001;Yamaguchi et al, 2001;Yamamura & Yokozawa, 2002). Such changes relate to range expansion, replacement of dominant species, seasonal phenology and occurrence of potential crop pests.…”
Section: Introductionmentioning
confidence: 99%
“…These predictions are particularly relevant in a world disturbed by ongoing climatic changes (Yamaguchi et al 2001;Williams and Liebhold 2002;Kiritani 2006;Thuiller et al 2006) and by the increasing exchange of goods and people (McNeely 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Two different approaches have been applied to project the influence of global warming on insects-estimating an increase in the number of generations using a formula based on effective temperature (Yamamura and Kiritani, 1998) and examining a change in the phenology and occurrence of pests using field survey data collected in years with an unusually high temperature (Yamaguchi et al, 2001). Although the influence of global warming on S. dorsalis populations is presently unclear, the regression line obtained in the present study would be helpful in predicting the changes in the life cycle of S. dorsalis caused by global warming if census data can be related to the actual field conditions.…”
Section: Discussionmentioning
confidence: 99%